Exploring the Impact of Organizational Support, Perceived Productivity, and Employee Status on the Organizational Commitment during the Mandatory Telework of COVID-19 Pandemic: Empirical Evidence with Algerian Employees - Serradj, Toufik; Saidani, Amal (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
This study investigates the impact of mandatory teleworking during the coronavirus disease 2019 (COVID-19) pandemic on organizational commitment (OC) among employees in Algeria. A sample of 408 respondents were utilized, consisting of employees from public sector companies in Algiers. Data were collected through an online questionnaire, and the methodology employed is quantitative, using statistical analysis to examine the relationship between teleworking conditions and levels of OC. The results highlight significant associations between commitment levels and factors such as teleworking duration, perceived employer support, perceived productivity, and employee status. This research adds to the existing literature by examining the unique challenges faced by employees during mandatory teleworking, particularly in Algeria, where teleworking practices are still emerging. The study provides practical recommendations for organizations to strengthen employee commitment as they navigate the evolving work environment.